1996
DOI: 10.1136/jmg.33.8.655
|View full text |Cite
|
Sign up to set email alerts
|

PAX genes and human neural tube defects: an amino acid substitution in PAX1 in a patient with spina bifida.

Abstract: From studies in the mouse and from the clinical and molecular analysis of patients with type 1 Waardenburg syndrome, particular members of the PAX gene family are suspected factors in the aetiology of human neural tube defects (NTD). To investigate the role of PAXI, PAX3, PAX7, and PAX9, allelic association studies were performed in 79 sporadic and 38 familial NTD patients from the Dutch population. Sequence variation was studied by SSC analysis of the paired domain regions of the PAXI, PAX7, and PAX9 genes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(31 citation statements)
references
References 26 publications
0
30
0
1
Order By: Relevance
“…PAX3 eksikliği olan farelerde spina bifida oluştuğu ve başka birçok nöral krest anomalilerinin ortaya çıktığı gösterilmiştir (1,5,26) . Literatürde NTD hastalarında PAX3 polimorfizmlerinin araştırıl-dığı çalışma sayısı oldukça sınırlıyken TEAD2 gen polimorfizmlerin incelendiği çalışmaya rastlanmamıştır (9,31) . Çalışmamızda TEAD2 genotipleri ve allel sıklıkları açısından hasta ve kontrol grupları arasında anlamlı bir fark görülmemiştir.…”
Section: Discussionunclassified
“…PAX3 eksikliği olan farelerde spina bifida oluştuğu ve başka birçok nöral krest anomalilerinin ortaya çıktığı gösterilmiştir (1,5,26) . Literatürde NTD hastalarında PAX3 polimorfizmlerinin araştırıl-dığı çalışma sayısı oldukça sınırlıyken TEAD2 gen polimorfizmlerin incelendiği çalışmaya rastlanmamıştır (9,31) . Çalışmamızda TEAD2 genotipleri ve allel sıklıkları açısından hasta ve kontrol grupları arasında anlamlı bir fark görülmemiştir.…”
Section: Discussionunclassified
“…30 To support this hypothesis, a missense mutation in a conserved region of the PAX1 paired box has been described in a foetus with a neural tube defect. 31 The mutation Q42H (Q115H in our sequence) was inherited through an unaffected mother and grandmother. A phenotype reminiscent of extreme spina bifida occulta in humans is also seen in mice doubly mutant for undulated and Patch.…”
Section: Discussionmentioning
confidence: 99%
“…This is also revealed by functional assays performed for 2 of the 6 mutations. For the PAX1 mutation it could be demonstrated that it diminished the affinity of the protein for binding to its target DNA sequences [17,33] . One of the VANGL1 mutations was shown to abolish the complexation with its normal binding partners.…”
Section: Neural Tube Defects: Sequencing Of Candidate Genes To Find Hmentioning
confidence: 99%